Association between baseline blood pressure variability and left heart function following short‐term extreme cold exposure - Chen, Renzheng; Yang, Qian; Wang, Yabin; Fang, Yan; Cao, Feng (The journal of clinical hypertension (Greenwich, Conn.), 2024)
Extreme cold exposure has been widely considered as a cardiac stress and may result in cardiac function decompensation. This study was to examine the risk factors that contribute to changes in cardiovascular indicators of cardiac function following extreme cold exposure and to provide valuable insights into the preservation of cardiac function and the cardiac adaptation that occur in real‐world cold environment. Seventy subjects were exposed to cold outside (Mohe, mean temperature −17 to −34°C) for one day, and were monitored by a 24‐h ambulatory blood pressure device and underwent echocardiography examination before and after extreme cold exposure. After exposure to extreme cold, 41 subjects exhibited an increase in ejection fraction (EF), while 29 subjects experienced a decrease. Subjects with elevated EF had lower baseline coefficients of variation (CV) in blood pressure compared to those in the EF decrease group. Additionally, the average real variability (ARV) of blood pressure was also significantly lower in the EF increase group. Multivariate regression analysis indicated that both baseline CV and ARV of blood pressure were independent risk factors for EF decrease, and both indicators proved effective for prognostic evaluation. Correlation analysis revealed a correlation between baseline blood pressure CV and ARV, as well as EF variation after exposure to extreme cold environment. Our research clearly indicated that baseline cardiovascular indicators were closely associated with the changes in EF after extreme cold exposure. Furthermore, baseline blood pressure variability could effectively predict alterations in left cardiac functions when individuals were exposed to extreme cold environment.